Circadian rhythm‐related genes: implication in autoimmunity and type 1 diabetes. (September 2015) - Lebailly, B.; Boitard, C.; Rogner, U. C.
Abstract : Recent gene association and functional studies have proven the implication of several circadian rhythm‐related genes in diabetes. Diabetes has been related to variation in central circadian regulation and peripheral oscillation. Different transcriptional regulators have been identified. Circadian genes are clearly implicated in metabolic pathways, pancreatic function and in type 2 diabetes. Much less evidence has been shown for the link between circadian regulation and type 1 diabetes. The hypothesis that circadian genes are involved in type 1 diabetes is reinforced by findings that the immune system undergoes circadian variation and that several autoimmune diseases are associated with circadian genes. Recent findings in the non‐obese diabetic mouse model pinpoint to specific mechanisms controlling type 1 diabetes by the clock‐related gene Arntl2 in the immune system.